Co-production in healthcare: rhetoric and practice. (March 2016) - Vennik, Femke D.; van de Bovenkamp, Hester M.; Putters, Kim; Grit, Kor J.
Co-production in healthcare is receiving increasing attention; however, insight into the  process  of co-production is scarce. This article explores why hospitals involve patients and staff in co-production activities and hospitals' experiences with co-production in practice. A qualitative study with semi-structured interviews ( N  = 27), observations (70 hours) and document analysis was conducted in five Dutch hospitals, which involved patients and staff in order to improve services. The results show that hospitals have different motives to involve patients and staff and have adapted existing methods to involve patients. Interestingly, areas of improvement proposed by patients were often already known. However, the process of co-production did contribute to quality improvement in other ways. The  process of co-production  stimulated hospitals' thinking about how to realize quality improvements. Quality improvements were facilitated by this process as seeing patients and hearing their experiences created a sense of urgency among staff to act on the improvement issues raised. Moreover, the experiences served to legitimatize improvements to higher management bodies. Points for practitioners: Different participation methods can bring patients' experiences with healthcare services to the fore, which can be used for quality improvement. Our study shows that adapting existing methods to local hospital resources is likely to be beneficial for co-production processes within a given context. However, adapting and tailoring also poses risks. Tailoring activities, such as using criteria to select patients, influence what is considered to be legitimate patient input. In addition, as the co-production process is important, the method should consist of an organized trajectory in which patients and staff are involved and personal experiences are presented. Therefore, project teams need to critically reflect on the consequences of adaptations and tailoring actions, and their desirability, when carrying out quality improvement projects.